Experiences of Stigma and Support Reported by Participants in a Network Intervention to Reduce HIV Transmission in Athens, Greece; Odessa, Ukraine; and Chicago, Illinois - Williams, L. D.; Korobchuk, A.; Pavlitina, E.; Nikolopoulos, G K; Skaathun, B.; Schneider, J.; Kostaki, E. G.; Smyrnov, P.; Vasylyeva, T. I.; Psichogiou, M; Paraskevis, D; Morgan, E.; et al. (AIDS BehavAIDS BehavAIDS Behav, 2019)
A growing body of evidence suggests that network-based interventions to reduce HIV transmission and/or improve HIV-related health outcomes have an important place in public health efforts to move towards 90-90-90 goals. However, the social processes involved in network-based recruitment may pose a risk to participants of increasing HIV-related stigma if network recruitment causes HIV status to be assumed, inferred, or disclosed. On the other hand, the social processes involved in network-based recruitment to HIV testing may also encourage HIV-related social support. Yet despite the relevance of these processes to both network-based interventions and to other more common interventions (e.g., partner services), there is a dearth of literature that directly examines them among participants of such interventions. Furthermore, both HIV-related stigma and social support may influence participants' willingness and ability to recruit their network members to the study. This paper examines (1) the extent to which stigma and support were experienced by participants in the Transmission Reduction Intervention Project (TRIP), a risk network-tracing intervention aimed at locating recently HIV-infected and/or undiagnosed HIV-infected people and linking them to care in Athens, Greece; Odessa, Ukraine; and Chicago, Illinois; and (2) whether stigma and support predicted participant engagement in the intervention. Overall, experiences of stigma were infrequent and experiences of support frequent, with significant variation between study sites. Experiences and perceptions of HIV-related stigma did not change significantly between baseline and six-month follow-up for the full TRIP sample, and significantly decreased during the course of the study at the Chicago site. Experiences of HIV-related support significantly increased among recently-HIV-infected participants at all sites, and among all participants at the Odessa site. Both stigma and support were found to predict participants' recruitment of network members to the study at the Athens site, and to predict participants' interviewer-rated enthusiasm for naming and recruiting their network members at both the Athens and Odessa sites. These findings suggest that network-based interventions like TRIP which aim to reduce HIV transmission likely do not increase stigma-related risks to participants, and may even encourage increased social support among network members. However, the present study is limited by its associational design and by some variation in implementation by study site. Future research should directly assess contextual differences to improve understanding of the implications of site-level variation in stigma and support for the implementation of network-based interventions, given the finding that these constructs predict participants' recruitment of network members and engagement in the intervention, and thereby could limit network-based interventions' abilities to reach those most in need of HIV testing and care.
Keywords: *Health Promotion; *Public Health; *Social Stigma; *Social Support; Adult; Chicago; Female; Greece; Health Knowledge, Attitudes, Practice; HIV Infections/*prevention & control/psychology/*transmission; Humans; Male; Mass Screening; Ukraine; Young Adult